Application of groundwater aggressiveness assessment method for estimation of the karst process at main gas pipeline construction; IOP Conference Series: Earth and Environmental Science; Vol. 33 : Contemporary Issues of Hydrogeology, Engineering Geology and Hydrogeoecology in Eurasia - Ermolaeva A. V. (Geology, Hydrogeology and Engineering Geology, 2016)
Title screen